Hacia una cultura estadística : aprendizaje de las medidas de dispersión en un contexto rural (2021)
Eng: The present work was carried out with the objective of analyzing the way in which project-based learning of dispersion measures can contribute to the development of the statistical culture of eleventh grade students in a rural context. To do so, we begin by addressing theoretically, among other topics, the teaching of statistics, dispersion measures, statistical culture and project-based learning. Then, following the qualitative methodological design, a diagnosis was made that showed the need to implement the project-based learning pedagogical strategy to address the topic of dispersion measures, seeking the use, interpretation and critical argumentation. With respect to the results of this process, it was concluded that, although significant achievements were reached regarding the development of a project and data management, due to situations such as social isolation, the expected levels of statistical culture were not reached, a situation that leaves as a major reflection, that when implementing this type of strategies, the interaction among students and the communication with the teacher is fundamental.